Childhood pesticide poisoning trend analysis of 13 years in Jiangsu, China - Wang, Boshen; Li, Xiuting; Han, Lei; Shen, Han; Zhang, Juan; Sun, Dawei; Gao, Dengfeng; Zhu, Bing; Zhu, Baoli (Journal of Public Health and Emergency; Vol 2 (December 2018): Journal of Public Health and Emergency, 2018)
Background: Childhood pesticide poisoning could be regarded as a critical communal health problem in different countries. The purpose of this research was to assess the occurrence probability of childhood pesticide poisoning in Jiangsu province and depict the relevant prevalent pathology features. Methods: From 2006 to 2017, a total of 1,373 cases of pesticide poisoning among children were reported in Jiangsu Province. The related materials and data were made in Excel Table and carefully analyzed by SAS relevant tool. Results: About 1,373 kids whose ages are 0–14 years were found in the pesticide poisoning examples who were reflected in Jiangsu Province in the research phase. The rate of occurrence from pesticide poisoning was 1.1 per 100,000 children every year. Organophosphorus and carbamate insecticides were seen as the reason of many poisons (504 out of 1,373). And most pesticide poisoning occurred in season summer [439] and autumn [433]. Conclusions: Pesticide poisoning is prevailing among kids in Jiangsu Province; thus, effective measures are very necessary for the reduction of the examples of childhood pesticide poisoning.